Targeting researchable problems - Reynolds, L. (Kenya Ministry of Livestock Development, 1991)
Examines research areas concerning sheep and goat production in the coastal subhumid zone of Kenya; with particular reference to the evaluation of the performance of and to the selection from within indigenous breeds; to health factors including trypanosomiasis, gastro-intestinal parasites and ear diseases; to nutrition and management studies; and to marketing and consumption of small ruminants.